Enhancing Students' Statistical Literacy Through Physical Education Long Jump Athletics Learning at Elementary School - Arsyad, Rahmatullah Bin; Bakar, Abu; Mardiah, Ainun; Al-lahmadi, Nazmi; Basna, Erik Norbertus (Universitas Muhammadiyah Mataram, 2025)
This study aims to improve elementary school students' statistical literacy through Physical Education (PJOK) learning, particularly in the long jump athletic material. The study used a quasi-experimental method with a pre-test post-test control group design. This research was conducted at SD Muhammadiyah 2 Kota Sorong with a total sample of 56 sixth-grade students, divided into two groups: the experimental class applying PJOK learning based on long jump athletics and the control class using a conventional learning model. Data were collected through pre-test, post-test, questionnaires, and observations of student activities. The results showed a significant improvement in statistical literacy in the experimental group compared to the control group. The t-test revealed a significance value indicating a significant difference between the two groups in achieving statistical literacy. The average N-Gain increase in the experimental group categorized as high, while the control group in moderate category. Additionally, students' responses to the learning model were positive. Based on these findings, it can be concluded that PE learning based on long jump athletics is effective in improving elementary students' statistical literacy. This learning model not only enhances conceptual understanding but also develops data analysis skills in real-world contexts.